The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s00464-015-4428-y
|View full text |Cite
|
Sign up to set email alerts
|

SAGES TAVAC safety and effectiveness analysis: da Vinci® Surgical System (Intuitive Surgical, Sunnyvale, CA)

Abstract: Gastrointestinal surgery with the da Vinci(®) Surgical System is safe and comparable, but not superior to standard laparoscopic approaches. Although clinically acceptable, its use may be costly for select gastrointestinal procedures. Current data are limited to the da Vinci(®) Surgical System; further analyses are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
45
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 137 publications
(115 reference statements)
1
45
0
1
Order By: Relevance
“…Despite the question of cost, use of the RC (both MPRC and SSRC) is considered appropriate in training for more complex abdominal operations (20). As one of the most commonly performed operations in general surgery and one of the few with a standardized approach for maintaining safety, the LC is almost an ideal operation for transitioning into robotic surgery.…”
Section: Robotic Cholecystectomy As a Tool For Trainingmentioning
confidence: 99%
“…Despite the question of cost, use of the RC (both MPRC and SSRC) is considered appropriate in training for more complex abdominal operations (20). As one of the most commonly performed operations in general surgery and one of the few with a standardized approach for maintaining safety, the LC is almost an ideal operation for transitioning into robotic surgery.…”
Section: Robotic Cholecystectomy As a Tool For Trainingmentioning
confidence: 99%
“…However, expert panels have found that although safe and comparable, the da Vinci robot is not in general superior to 2D laparoscopy. 3 This article proposes that the battery of clinically relevant measures used in clinical trials may vary as a function of more basic perceptual processes, such as stereoscopic acuity and resilience to perceptual conflicts associated with 3D displays. We describe both factors in detail and highlight how failure to control for individual surgeon differences may obscure the advantage of 3D robotic surgery over conventional 2D laparoscopic surgery.…”
mentioning
confidence: 99%
“…The first is the work product of the Society of American Gastrointestinal and Endoscopic Surgeons (SAGES) Technology and Value Assessment Committee on the da Vinci Ò Surgical System [1]. As a society, SAGES believes one of its missions is to provide documents putting forth opinions and judgments regarding new technology.…”
mentioning
confidence: 99%
“…Upon publication of the da Vinci system assessment [1], Myriam Curet, MD, FACS, SVP & Chief Medical Officer, Intuitive Surgical, Inc., requested the opportunity to respond to the SAGES analysis. Given the significance of the issue, and the spectrum of strong opinions held regarding robotic surgery, the editors have chosen to provide Dr. Curet with the opportunity to respond in writing.…”
mentioning
confidence: 99%
See 1 more Smart Citation